EMPIRICAL ANALYSIS TO ASSESS VIABILITY OF JABLITE'S CURRENT RESOURCES AND CAPABILITIES IN COMMERCIAL ROOF INSULATION. - Singh, Avneeta (2013)
Jablite Ltd is a 40 year old UK based well-known EPS insulation manufacturer that was taken over by a Dutch holding company, Synbra Group B.V., in the year 1996. During 2003 to 2011 Jablite had 7 different Managing Director and this had a direct impact on its competitive landscape. The things turned more difficult when it had to manage these internal challenges along with the 2007 recession and it’s after effects. After a going through a period when it was making profits as low as – £200,000 every month, the performance started picking up only in late 2011 and the top management became more stable. With a risk averse attitude and an intention to re-establish itself in UK insulation industry, Jablite is continuously making efforts to be the preferred EPS insulation supplier.